Carbon Dioxide Distribution, Origins, and Transport Along a Frontal Boundary During Summer in Mid‐Latitudes. Issue 9 (6th May 2021) - Samaddar, Arkayan; Feng, Sha; Lauvaux, Thomas; Barkley, Zachary R.; Pal, Sandip; Davis, Kenneth J.
Abstract: Synoptic weather systems are a major driver of spatial gradients in atmospheric CO2 mole fractions. During frontal passages, air masses from different regions meet at the frontal boundary creating significant gradients in CO2 mole fractions. We quantitatively describe the atmospheric transport of CO2 mole fractions during a mid‐latitude cold front passage and explore the impact of various sources of CO2 . We focus here on a cold front passage over Lincoln, Nebraska on August 4th, 2016 observed by aircraft during the Atmospheric Carbon and Transport‐America campaign. A band of air with elevated CO2 was located along the frontal boundary. Observed and simulated differences in CO2 across the front were as high as 25 ppm. Numerical simulations using Weather Research and Forecasting Model with Chemistry at cloud resolving resolutions (3 km), coupled with CO2 surface fluxes and boundary conditions from CarbonTracker (CT‐NRTv2017x), were performed to explore atmospheric transport at the front. Model results demonstrate that the frontal CO2 difference in the upper troposphere can be explained largely by inflow from outside of North America. This difference is modified in the atmospheric boundary layer and lower troposphere by continental surface fluxes, dominated in this case by biogenic and fossil fuel fluxes. Horizontal and vertical advection are found to be responsible for the transport of CO2 mole fractions along the frontal boundary. We show that cold front passages lead to large CO2 transport events including a significant contribution from vertical advection, and that midcontinent frontal boundaries are formed from a complex mixture of CO2 sources. Key Points: High resolution simulation of a cold front passage captures the narrow band of elevated CO2 ahead of the cold front CO2 inflow from the continental boundaries along with biogenic fluxes create the summertime frontal CO2 distribution Horizontal and vertical advection dominate atmospheric CO2 transport along the frontal boundary